The Contribution of Principal Leadership and School Culture to the Implementation of School-Based Management in Padang City Public Junior High School - Irsyad Irsyad; Nafisah Nafisah; Sulastri Sulastri; Syahril Syahril (CV. AFDIFAL MAJU BERKAH, 2023)
Based on observations in the field, it is illustrated that the implementation of school-based management in Padang City Public Junior High Schools has not been implemented properly. This is thought to have something to do with the principal's leadership and school culture. Therefore it is necessary to do research to test the truth. This study aims to reveal the contribution of the principal's leadership and school culture to the implementation of school-based management in Padang City Public Junior High School. The hypotheses put forward in this study are: 1) the principal's leadership contributes to the implementation of school-based management, 2) school culture contributes to the implementation of school-based management, 3) the principal's leadership and school culture together contribute to the implementation of school-based management. school based.The population in this study were all 116 deputy principals of state junior high schools in Padang City. The research sample consisted of 70 people who were taken using the Proportional Stratified Random Sampling technique, taking into account the level of education and years of service. The research instrument used is the rating scale and the Likert Scale model questionnaire which has been tested for its validity and reliability. The results of the validity test showed that 3 items were dropped, in the Y variable there was one item, namely item number 12, in the X1 variable, 1 item was dropped, namely number 28 and in the X2 variable, the item that was dropped was number 16. Furthermore, the research data was analyzed using correlation techniques and regression.The results of the data analysis show that: 1) principal leadership contributes to the implementation of school-based management by 41%, 2) school culture contributes to the implementation of school-based management by 28.4%, 3) principal leadership and school culture together contributed to the implementation of school-based management by 70.3%. The achievement level of the school-based management implementation score of 83.58% is in the good category, and for school principal leadership 83.65% is in the good category while for school culture 86.24 from the ideal score is in the good category.The findings above imply that the leadership of school principals and school culture are two factors that can improve the implementation of school-based management, apart from other factors.